A Landscape for the Sultan, an architecture for the eye: Edirne and its fifteenth-century royal tower. (2nd July 2016) - Kontolaimos, Panagiotis
ABSTRACT: This present essay is about the visibility properties of Early Modern Ottoman architecture and its contribution to the formation of a politically and culturally significant landscape. By using the royal tower of Edirne (Cihannüma Kasri), a structure of the mid-fifteenth century, as a case study, the impact of architecture in the visualisation of the cultural and political meanings of Ottoman urban and rural landscape is explored in an effort to reveal the interconnections between architectural design and landscape during the Early and Classical Ottoman Period (fifteenth– sixteenth centuries). This task is assisted by a variety of imagery that narrates the history of the royal tower as well as its interconnection with other aspects of its built and natural environment, thus visualising a unique assembly of meanings and spatial properties. Furthermore, this view is related to comparable developments in Renaissance Italy, thus seeing the relevant Ottoman developments within the context of wider socio-economic changes in the fourteenth– fifteenth-century Mediterranean.